2020
DOI: 10.1159/000509976
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Bidirectional Relationships between Sleep Disorder and Frequency of Nocturia: Results from the Iwaki Health Promotion Project

Abstract: <b><i>Introduction:</i></b> The causal relationship between sleep disorder and frequency of nocturia remains unclear. <b><i>Methods:</i></b> We longitudinally evaluated sleep disorder and frequency of nocturia in 547 community-dwelling adults between baseline and 5-year follow-up. We included participants ≥50 years old who have no sleep disorder (the Pittsburgh Sleep Quality Index [PSQI] ≥ 5) nor nocturia (≥1). For 5 years, we evaluated the temporal changes in sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…‘Nocturia is a result of sleep disorder because of high oxidative stress’ can be speculated because several previous studies suggested that sleep problems may be a key factor for preceding nocturia. 13 , 14 , 15 , 28 Although this connection could not be directly proven, the results may support the concept that nocturia is one of the consequences of the ageing syndrome (e.g., comorbidities and higher AGEs). However, there is not enough evidence to address this point.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…‘Nocturia is a result of sleep disorder because of high oxidative stress’ can be speculated because several previous studies suggested that sleep problems may be a key factor for preceding nocturia. 13 , 14 , 15 , 28 Although this connection could not be directly proven, the results may support the concept that nocturia is one of the consequences of the ageing syndrome (e.g., comorbidities and higher AGEs). However, there is not enough evidence to address this point.…”
Section: Discussionmentioning
confidence: 63%
“…'Nocturia is a result of sleep disorder because of high oxidative stress' can be speculated because several previous studies suggested that sleep problems may be a key factor for preceding nocturia. [13][14][15]28 Although this connection could not be directly proven, the results may support the concept that nocturia is one of the consequences of F I G U R E 1 Selection of participants and stratification for AGEs-low and -high groups. This study longitudinally evaluated the AGEs level, sleep disorders and nocturia frequency in 447 community-dwelling adults for 5 years.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations